2011
DOI: 10.1111/j.1521-0391.2011.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

“High on My Own Supply”: Correlates of Drug Dealing among Heterosexually Identified Methamphetamine Users

Abstract: Although rates of methamphetamine use continue to increase throughout the United States, little is known about the individuals who sell methamphetamine at the street level. This exploratory study examined the prevalence and correlates of drug-dealing behavior in a sample of 404 heterosexually-identified methamphetamine users who were participants in a sexual risk reduction intervention in San Diego, CA. Twenty-nine percent of participants (N = 116) reported “dealing” methamphetamine in the past two months. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 44 publications
(53 reference statements)
3
30
0
1
Order By: Relevance
“…This is supported by a prior study that found an association between more frequent crystal methamphetamine use and crystal methamphetamine injection with drug dealing in a cohort of methamphetamine users (40). The association between dealing drugs and initiation of crystal methamphetamine may represent several factors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is supported by a prior study that found an association between more frequent crystal methamphetamine use and crystal methamphetamine injection with drug dealing in a cohort of methamphetamine users (40). The association between dealing drugs and initiation of crystal methamphetamine may represent several factors.…”
Section: Discussionsupporting
confidence: 80%
“…The association between dealing drugs and initiation of crystal methamphetamine may represent several factors. First, drug dealers may be more likely to use the drugs they are selling, especially as many drug users sell drugs to support their own drug use (40,41). Secondly, drug dealing often occurs in a hostile, violent environment and crystal methamphetamine use may help dealers cope in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, street-involved youth who use crystal methamphetamine were found to be more likely to initiate drug dealing; previous research has suggested that this substance’s stimulant effect and the associated need for repeated use may create a financial need to deal drugs (5,2224). This interpretation may be especially applicable to our sample of street-involved youth, as 38% of those who use crystal methamphetamine did so on a daily basis, a level of use that may create a significant financial burden.…”
Section: Discussionmentioning
confidence: 52%
“…However, there is no indication that receipt of social assistance increases overall drug use above unabated poverty (Rosen, 2011). Participation in drug dealing has been associated with elevated risks of overdose and frequent drug use in addition to violence, HIV infection, and incarceration (Curry & Latkin, 2003; Latkin, 2002; Semple et al, 2011; Small et al 2013; Werb et al, 2008). Among female sex workers, the amount of income generated through sex work has been found to be independently correlated with the amount of money spent on drugs and higher income from sex work has been connected to elevated odds of high risk drug use (Deering et al, 2011; Rekart, 2006; Shannon et al, 2008; Spice, 2007).…”
Section: Discussionmentioning
confidence: 99%